Cytokines and CD4 T Cells: dance partners at the immunology ball - Paul, William E. (Henry Stewart Talks, 2012)
Naive CD4 T cells differentiate into various Th effector classes, Each Th cell type has a specific function in responding to infectious agents, Differentiated states may be plastic, Cytokine activated cytokine production, Epigenetic regulation of Th differentiation